Recruiting - Petersen, A.; Wagner, K.; Greener, T. (Strength and Conditioning Journal, 2012)
In most intercollegiate athletic programs, success is based on wins and losses. As a result, successful recruiting is paramount. Because of the importance of recruiting at the collegiate level, our panel of strength and conditioning coaches were asked what role they play in the recruiting process at their respective institutions.